GAMBARAN PENGETAHUAN GIZI ORANG TUA DAN KEJADIAN STUNTING PADA ANAK SEKOLAH DASAR - Fendri Ismail; M. Anas Anasiru; Rahma Labatjo; Sofyawati D. Talibo (Jurusan Gizi Politeknik Kesehatan Gorontalo, 2022)
Nutrition knowledge is knowledge about the role of nutrition, nutrients, sources of nutriens in food, foods that are safe to eat so it does not cause disease, and how to process food properly so that nutrients in food are not lost and how to live a healthy life. Besides, stunting is the impact of various factors such as low birth weight, inappropriate stimulation and parenting, inadequate nutrients intake, recurrent infection, and other assorted environmental factors. The research aims to discover the overview of parental nutrition knowledge and stunting incidents in school children in Pauwo Village, Kabila Subdistrict, Bone Bolango Distirict. The research method applies a descriptive survey, namely a survey conducted to describe the variable examined. The population in this research is the whole elementary school stundents in Pauwo Village, Kabila Subdistrict, Bone Bolango District, Which is amounted to 147 students, while the samples taken are 34 students. The independent variable are parental nutrition knowledge and stunting incidents in school children in Pauwo Village, Kabila Subdistrict, Bone Bolango District. Finding discloses that parental knowledge with a good category is 85% and less good category is 15,0%. Whereas the stunting incident status in school children in Pauwo Village, Kabila Subdsitrict, Bone Bolango district indicates that a child (5,0%) is stunting, 30 children (80%) are normal, and three children (15%) are tall. In conclusion, parental nutrition knowledge is mostly in the good category and stunting incidents in elementary school students in Pauwo Village, Kabila Subdistrict, Bone Bolango District is 5%.Pengetahuan gizi merupakan pengetahuan tentang peranan dan zat gizi, sumber- sumber zat gizi pada makanan, makanan yang aman untuk dimakan sehingga tidak menimbulkan penyakit dan cara mengolah makanan yang baik agar zat gizi dalam makanan tidak hilang, serta bagaimana cara hidup sehat. Stunting merupakan dampak dari berbagai faktor seperti berat badan lahir rendah, stimulasi dan pengasuhan anak yang kurang tepat, asupan nutrisi kurang dan infeksi yang berulang, serta berbagai faktor lingkungan lainnya. Penelitian ini bertujuan untuk mengetahui gambaran Pengetahuan gizi orang tua dan terjadinya stunting pada anak sekolah dasar Di Kelurahan Pauwo Kecamatan Kabila Kabupaten Bone Bolango. Metode penelitian ini menggunakan survey deskriptif, yaitu survey yang dilakukan untuk menggambarkan variable yang diteliti. Populasi yaitu seluruh siswa di sekolah dasar Kelurahan Pauwo Kecamatan Kabila Kabupaten Bone Bolango yang berjumlah 147 siswa, sampel yang diambil yaitu berjumlah 34 orang. Variabel mandiri yaitu gambaran Pengetahuan gizi orang tua dan terjadinya stunting pada anak sekolah dasar di Kelurahan Pauwo Kecamatan Kabila Kabupaten Bone bolango. Hasil penelitian menunjukkan pengetahuan dengan kategori baik (85,0%) dan kategori kurang baik (15,0%), Status kejadian stunting anak sekolah dasar Di Kelurahan Pauwo Kecamatan Kabila Kabupaten Bone Bolango bahwa sebanyak 1 orang (5,0%) memiliki status gizi pendek, sedangkan yang normal 30 orang (80,0%) dan 3 orang (15,0%) tinggi.